ANALISIS DAMPAK NEGATIF PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP AKHLAK SANTRIWATI KELAS 10 MA MA’AHID KUDUS - Diniarti; Muhammad Abdullah Darraz (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
The progress and development of information technology has many positive impacts and negative impacts. Judging from the soaring popularity of social media applications that provide entertainment platforms among students at this time, the use of social media actually has a lot of positive impacts on students, but there are also many negative impacts of social media for student behavior and morals. This study aims to analyze the negative impact of using TikTok social media on student morals. This research uses qualitative methods used to research and get answers to existing problems. Data collection techniques carried out by researchers are by observation and interviews. The basic core of the information is the interview results of grade 10 students and ustadzah MA Ma'ahid Kudus. The results of this study show that the use of TikTok social media has a negative impact on grade 10 MA Ma'ahid students which makes students become addicted and lazy, other negative impacts such as students using the TikTok application as an entertainment medium to dance and then publish on social media, a lot of inappropriate speech, with these negative impacts, a solution is needed to overcome the negative impact of using social media TikTok is like controlling yourself by using time well and the existence of direction, knowledge from teachers or ustadzah on TikTok social media.